Sobetirome rescues α-synuclein-mediated demyelination in an in vitro model of multiple system atrophy - Meszaros, Lisa; Himmler, Marcus; Schneider, Yanni; Arnold, Philipp; Dörje, Frank; Schubert, Dirk W.; Winkler, Jürgen (European Journal of Neuroscience, 2023)
Multiple system atrophy (MSA) is a rare and rapidly progressive atypical parkinsonian disorder characterized by oligodendroglial cytoplasmic inclusions containing α-synuclein (α-syn), demyelination, inflammation and neuronal loss. To date, no disease-modifying therapy is available. Targeting α-syn-driven oligodendroglial dysfunction and demyelination presents a potential therapeutic approach for restricting axonal dysfunction, neuronal loss and disease progression. The present study investigated the promyelinogenic potential of sobetirome, a blood–brain barrier permeable and central nervous system selective thyromimetic in the context of an in vitro MSA model. Oligodendrocyte precursor cells (OPCs) were obtained from transgenic mice overexpressing human α-syn specifically in oligodendrocytes (MBP29 mouse line), a well-described MSA model, and non-transgenic littermates. mRNA and protein expression analyses revealed a substantial rescue effect of sobetirome on myelin-specific proteins in control and α-syn overexpressing oligodendrocytes. Furthermore, myelination analysis using nanofibres confirmed that sobetirome increases both the length and number of myelinated segments per oligodendrocyte in primary murine α-syn overexpressing oligodendrocytes and their respective control. These results suggest that sobetirome may be a promising thyromimetic compound targeting an important neuropathological hallmark of MSA.
CRIS-Team Scopus Importer:2023-12-22
Keywords: MSA; myelin; oligodendrocytes; sobetirome; thyromimetics; α-synuclein